Trend Map: A Bibliometric Exploration of the Utilization of Chemical Education Bulletins in the Digital Age - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (Universitas Papua, Manokwari, Indonesia, 2024)
A bibliometric analysis of research on the theme of chemical education bulletin from 2020 to 2024 found 49 scientific articles published during the period. The 365 total citations, with an average of 7.45, indicate that this research has been widely discussed and noticed in other scientific literature. The main results show that the trend of scientific research for the term